Maternal crises and the role of African men: the case of a Nigerian community (2007)
Studies have consistently shown that maternal processes in Africa are prone to crises as a result of multiple socio-economic and religious factors. A combination of male-domination, low status of women, poverty, cultural beliefs and practices and high fertility affects pregnancy outcomes in most societies in the continent and especially in sub-Saharan Africa. With very few exceptions, African communities are patriarchal and as such norms, values and expectations are defined and sustained by men in virtually all spheres of life. This paper, which focuses on the Ibani of Rivers State, Nigeria, examines the role of African men during maternal periods to establish that pregnancy outcomes will improve significantly when women are supported by their spouses at different stages of maternity. The study reveals that men do not play roles during pregnancy-postpartum processes that are significantly different from their normal activities because pregnancy is perceived as a normal condition, which does not require special attention. The results also indicate that pregnancy outcomes among the Ibani do not necessarily derive from spousal communication and gender discourse because 87.7 percent of women whose husbands were solely responsible for decisions on child spacing recorded more Type-1 outcome (mother and child survival) than those whose husbands did not. By adapting the present investigation to the systemic approach, a holistic analysis of a complex phenomenon like maternal outcomes was undertaken.